(untitled) (Experimental biology, 2020)
Rickettsia typhi (R. typhi) belongs to the typhus group rickettsiae and causes endemic typhus. Human infection can occur alimentary (consumption of food contaminated with rat feces), through rat fleas (infected flea bites, inhalation of dried flea feces), as well as through ticks that parasitize on rats (infection occurs when a person is bitten by an infected tick). Cases of endemic typhus and seropositivity to R. typhi have been reported in the neighboring China and Russia, nevertheless little is known of the endemic typhus in Kazakhstan. The purpose of this study was to evaluate the prevalence of specific antibodies to R. typhi in the population of the southern region of Kazakhstan. A total of 253 individuals (142 women, 111 men) aged from 1 to 71 years were recruited into the study. Detection of serum IgG antibodies against R. typhi was performed by ELISA. IgG antibodies to R. typhi were detected in 34.4% of the analyzed population. High prevalence was detected in the Turkistan oblast (91.8% on average in the oblast) and in the village of Zhalandy, Almaty oblast (31.9% of all individuals). The seroprevalence was identical in both sexes. Seropositivity was not significantly associated with age, but positive results were not detected in the age group of children under 14 years. The obtained results confirm active circulation of R. typhi in the Turkistan and Almaty oblast of Kazakhstan, which in turn indicates an urgent need for further study of the role of endemic typhus in the structure of fever of unknown origin in the southern region of Kazakhstan. Key words: Rickettsia typhi, Southers region of Kazakhstan, class G immunoglobulins.